Sphenoid Wing Dysplasia in the Absence of Neurofibromatosis: Diagnosis and Management of a Novel Phenotype - Zapatero, Zachary D. (Plast Reconstr Surg Glob Open, 2021)
Congenital sphenoid wing dysplasia is one of the major diagnostic criteria for neurofibromatosis type 1, and is often considered pathognomonic for the disease. Between 5% and 12% of neurofibromatosis type 1 cases have evidence of sphenoid wing dysplasia. Sequelae of this deficiency include slow expansion of the middle temporal fossa and progressive herniation of the temporal lobe into the orbital cavity, resulting in pulsatile exophthalmos. Herein, we report a patient with greater sphenoid wing agenesis and middle temporal fossa enlargement requiring transcranial orbital reconstruction in the absence of neurofibromatosis. To our knowledge, this represents a novel craniofacial phenotype of sphenoid wing agenesis in the absence of neurofibromatosis previously not described in the literature.